Exploring types of deviant workplace behavior in a public organization in Malaysia - Sathappan, Malini; Omar, Zoharah; Ahmad, Aminah; Hamzah, Azimi; Ismail, Ismi Arif (Council for Innovative Research, 2016)
Deviant workplace behavior among employees is becoming a universal issue at various organizations, not excluding enforcement agencies. Deviant behavior need to be studied by scholars to prevent detrimental effects such as job dissatisfaction, intention to quit, stress, decreased productivity, loss of work time, high turnover rate and financial costs among employees. The purpose of this paper is to explore the types of deviant workplace behavior in the government sector in Malaysia. Data collection for the research was carried out by interviewing 14 law enforcement officers in Malaysia. This study involves various departments. The study found that there are various types of misconduct existing at the organization e.g. bribery, uninformed polygamy, drugs, on-line gambling, absenteeism, and lateness. This study also provided a framework on types of misconduct to the enforcement agency.